Ds+ exclusive hadronic decays involving ω - Ge, J; Miller, D; Shipsey, I; Xin, B; Adams, G; Hu, D; Moziak, B; Napolitano, J; Ecklund, K; He, Q; Insler, J; Muramatsu, H; et al. (2009)
Using data collected near the Ds* ± Ds Ds peak production energy E cm 4170 MeV by the CLEO-c detector, we search for Ds+ exclusive hadronic decays involving. We find B Ds+ n+ w 0.21 ± 0.09 ± %, B Ds+ n+ 2.78 ± 0.65 ± 0.25 %, Ds+ n+ n+ n- 1.58 ± 0.09%. Ds+ n+ 0.85± 0.54 ± 0.06%. K+. n+ n- 0.54%, and The upper limits are at 90% confidence level.